The Neurology of Death and the Dying Brain: A Pictorial Essay - Kondziella, Daniel (Frontiers in Neurology, 2020)
As neurologists earn their living with the preservation and restoration of brain function, they are also well-positioned to address the science behind the transition from life to death. This essay in pictures highlights areas of neurological expertise needed for brain death determination; shows pitfalls to avoid during the clinical examination and interpretation of confirmatory laboratory tests in brain death protocols; illustrates the great variability of brain death legislations around the world; discusses arguments for the implementation of donation after circulatory death (DCD); points to unresolved questions related to DCD and the time between cardiac standstill and organ procurement (“hands-off period”); provides an overview of the epidemiology and semiology of near-death experiences, including their importance for religion, literature and the visual arts; suggests biological mechanisms for near-death experiences such as dysfunction of temporoparietal cortex, N-methyl-D-aspartate receptor antagonism, migraine aura and rapid eye movement sleep; hypothesizes that thanatosis (aka. death-feigning, a common behavioral trait in the animal kingdom) represents the evolutionary origin of near-death experiences; and speculates about the future implications of recent attempts of brain resuscitation in an animal model. The aim is to provide the reader with a thorough understanding that the boundaries within the neurology of death and the dying brain are being pushed just like everywhere else in the clinical neurosciences.